Nilai-Nilai Pendidikan Islam Dalam Ngagai Rupuk’An Suku Seraway - Bobby Kandana; M. Yogi Ramadhan (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRACT This study aims to find answers about the values of Islamic education in the performance of the Seraway tribe in Meranti Jaya Village, Ujanmas District, Kepahyang Regency, Bengkulu Province. This research method uses field research with a qualitative approach. Data collection techniques used in this study include observation, interviews and documentation. The results showed that the values of Islamic education contained in Ngagai Rupuk'An were moral education, sholawatan, marhaban, dzikir, religious lectures, social, reciting and reading Persanji books. The conclusion of this research is moral education, here the members of Ngagai Rupuk'an give an example to the community, namely by implementing morals or what we often call praiseworthy morals, for example, being willing to sacrifice, honest, polite, polite, fair, patient, and disciplined. Sholawatan, here the members of Ngagai Rupuk'An provide sholawatan education so that more and more of our prayer reading will be given intercession of the Prophet Muhammad at the end of the day. Keywords: Islamic education values, Ngagai Rupuk’an.